The Influence of Learning Environment and Learning Motivation on Learning Achievement in Economics Subject Class VIII SMP Negeri 2 Satap Aesesa - Asterius Yoseph Polo; Miftah Rakhmadian; Putri Vina Sefaverdiana (Program Studi Pendidikan Ekonomi, Universitas Insan Budi Utomo, 2021)
Any school at all levels, from the lowest to the highest, expects that every student who studies at the school can obtain satisfactory achievements. If this can be realized, it is a matter of pride for students and for the school. Learning achievement is changes in knowledge and understanding, as well as values, attitudes and skills possessed by students after they are involved or experience the learning process. Based on the results of a preliminary study conducted by researchers on February 10, 2020 at the State Junior High School (SMP) Satap 2 Aesesa, it showed that the learning achievement of class VIII students in terms of the Final Semester Assessment (PAS) 1 economics subjects was still unsatisfactory, because the majority of the average grades the average class is still below the Minimum Learning Completeness Criteria (KKM) set by the teacher. This study aims to analyze the effect of the learning environment, learning motivation, on learning achievement. The sampling technique used is random sampling. The main data analysis technique used to test the research hypothesis is using multiple regression analysis. The results of this study are the independent learning environment variable has a positive and significant influence on the learning achievement variable. The independent learning motivation variable also has a positive and significant influence on the learning achievement variable on learning achievement. These two variables together also have a positive influence on learning achiev ement with a percentage of 53.6%, while the rest is influenced by other factors not included in this study